Research on the architectural space of folk houses in Guangxi Yao mountainous areas from the perspective of regional culture - Xu, Ying; Puntien, Pisit; Inkuer , Akapong; Mayusoh, Chanoknart (Journal of Roi Kaensarn Academi, 2024)
This study aims to explore the spatial characteristics and changes of residential buildings in Guangxi Yao mountainous areas from the perspective of regional culture. By comprehensively using on-site research, literature review, case studies, and interview research methods, this article conducts an in-depth analysis of the spatial layout and structural characteristics of Yao folk residential buildings in different geographical and cultural backgrounds. The research results reveal the profound influence of regional culture on the spatial design of residential buildings, and show how the characteristics and structure of architectural spaces develop and change with time and modern influences. In addition, the study also discussed the balance between residential architecture adapting to modern life and maintaining cultural heritage. This article proposes a series of strategies for the protection and development of residential buildings, emphasizing the importance of promoting cultural inheritance and regional identity. The research not only provides a theoretical basis for the protection and development of Yao residential buildings in Guangxi, but also provides valuable guidance for future research in related fields.